2019
DOI: 10.1111/jvh.13248
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the prevalence of occult HBV infection in Western Europe and in Northern America: A meta‐analysis

Abstract: Data on the prevalence of occult HBV infection (OBI) in Western Europe and in Northern America are few; hence, we conducted a systematic review and meta‐analysis. All studies included had to fulfil the following inclusion criteria: (a) they investigated the prevalence of OBI (HBV DNA in liver tissue in HBsAg‐negative subjects), (b) were carried out in Western Europe and in Northern America; (c) were available as a full‐text manuscript, (d) written in English and (e) published up to December 2018. The exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
(779 reference statements)
0
12
1
Order By: Relevance
“…A recent meta-analysis suggests an estimated OBI prevalence of 34% in anti-HBc-reactive individuals without chronic liver disease from Western Europe and North America based on detectable HBV DNA in liver tissue. 21 However, detectable HBV DNA in liver tissue does not equal HBV transmission risk through blood products. The infectivity of blood products correlates with higher viral loads in plasma, higher volumes of HBV DNA positive plasma transfused, and absence of anti-HBs in both donor and recipient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis suggests an estimated OBI prevalence of 34% in anti-HBc-reactive individuals without chronic liver disease from Western Europe and North America based on detectable HBV DNA in liver tissue. 21 However, detectable HBV DNA in liver tissue does not equal HBV transmission risk through blood products. The infectivity of blood products correlates with higher viral loads in plasma, higher volumes of HBV DNA positive plasma transfused, and absence of anti-HBs in both donor and recipient.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of MP‐NAT with increased analytical sensitivity (LOD MP‐NAT decreased from 23 to 7.8 IU/mL during the study period) did not result in a higher yield of confirmed OBI. A recent meta‐analysis suggests an estimated OBI prevalence of 34% in anti‐HBc‐reactive individuals without chronic liver disease from Western Europe and North America based on detectable HBV DNA in liver tissue 21 . However, detectable HBV DNA in liver tissue does not equal HBV transmission risk through blood products.…”
Section: Discussionmentioning
confidence: 99%
“…With another subanalysis of the same work, the prevalence of OBI was 51% (95% CI, 40-62%) in the 823 anti-HBc-positive subjects and 19% (95% CI, 10-30%) in the 1041 anti-HBc-negative subjects. 59 It is interesting to note that in patients with cryptogenic cirrhosis or advanced liver fibrosis, the prevalence ranges from 4% to 38%. 16,40,60 Considering the different populations studied, the prevalence is about 45% in the case of parenteral blood exposure, 61 in patients with chronic hepatitis C (CHC), it is estimated at about 52%, in HIV-infected patients it ranges from 0% to 45%, 62 in blood donors from 0% to 22.7% 63,64 and in hemodialysis patients from 0% to 54%.…”
Section: Search Strategymentioning
confidence: 99%
“…59 Moreover, in the same meta-analysis the authors also evaluated the role of the presence of anti-HBs in anti-HBc-positive subjects: the pooled overall prevalence of OBI was 43% (95% CI, 27-60%) in the 176 anti-HBs-negative/anti-HBcpositive subjects and 51% (95% CI, 31-72%) in the 257 anti-HBs/ anti-HBc-positive subjects. 59 Then, evaluating the data from studies comparing anti-HBc-positive and negative subjects, the authors found that the prevalence of OBI was higher in the 641 anti-HBc-positive subjects than in the 1041 anti-HBc-negative (prevalence ratio [PR], 2.29, 95% CI, 1.61-3.26; P < .001). 59 Finally, Table 4 summarizes studies evaluating OBI prevalence in a particular subgroup of patients, the anti-HBs positive and anti-HBc negative subjects.…”
Section: Prevalence Of Obi Defined As Hbv Dna Positivity In Liver Tissuementioning
confidence: 99%
“…In recent years, the increasing use of immunosuppressive treatments has led to a growing incidence of HBV reactivation (HBVr) in patients with overt or occult infection [ 3 ]. As a systematic review recently published by our group estimated a prevalence of OBI in Western countries ranging from 19% to 51% [ 4 ], and considering the incidence of immunosuppressive diseases and/or the use of immunosuppressive treatments, the risk of HBVr has become high.…”
Section: Introductionmentioning
confidence: 99%